# What is "x" 1.3x+4-8÷2×5-3+1=3 2.2x+6-12×3÷2+3×-20+5=6

1
by renny

2014-12-25T09:52:07+08:00

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Woah! This might take a long time but let us answer this by simplifying it first using the combination of terms. We should use the PMDAS and the left-to-right method if it is already pure Subtraction and Addition or pure Multiplication and Division.
Okay, number 1:

1.) 3x + 4 - 8 / 2 x 5 - 3 + 1 = 3
3x  + 4 - [(8/2) x 5] - 3 + 1 = 3
3x + 4 - [ (4) x 5 ] - 3 + 1 = 3
3x + 4 - 20 - 3 + 1 = 3
3x -16 - 3 + 1 = 3
3x - 19 + 1 = 3
3x -18 = 3
3x = 3 + 18
3x = 21
x = 7
Check:
3x + 4 - [ (8/2) x 5 ] - 3 + 1 = 3
3(7) + 4 - [(8/2) x 5] - 3 + 1 = 3
21 + 4 - [ 4 x 5 ] - 3 + 1 = 3
21 + 4 - 20 - 3 + 1 = 3
25 - 20 -3 + 1 = 3
5 - 3 + 1 = 3
2 + 1 = 3
3 = 3, CORRECT!!!

Number 2.

2.) 2x + 6 - 12 x 3 / 2 + 3x - 20 + 5 = 6
2x + 6 - [(12 x 3) / 2] + 3x - 20 + 5 = 6
2x + 6 - [ 36 / 2 ] + 3x - 20 + 5 = 6
2x + 6 - 18 + 3x - 20 + 5 = 6
2x - 12 + 3x - 20 + 5 = 6
5x - 12 - 20 + 5 = 6
5x - 32 + 5 = 6
5x - 27 = 6
5x = 6 + 27
5x = 33
x = 33/ 5

Check:
2x + 6 - [(12 x 3) / 2] + 3x - 20 + 5 = 6
2x + 6 - [ 36 / 2 ] + 3x - 20 + 5 = 6
2x + 6 - 18 + 3x - 20 + 5 = 6
2(33/5) + 6 - 18 + 3(33/5) - 20 + 5 = 6
66 / 5 - 12 + 99/5 - 20 + 5 = 6
165 / 5 - 32 + 5 = 6
165 / 5 - 27 = 6
165 / 5 = 6 + 27
165 / 5 = 33
33 = 33, CORRECT!!!